2014
DOI: 10.1111/hae.12344
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre, randomized, open‐label study of on‐demand treatment with two prophylaxis regimens of recombinant coagulation factor IX in haemophilia B subjects

Abstract: Few randomized studies have reported on the use of factor IX (FIX) for secondary prophylaxis in haemophilia B patients. This study aimed to evaluate the efficacy and safety of two secondary prophylaxis regimens of recombinant coagulation FIX, nonacog alfa, compared with on-demand therapy. Male subjects aged 6-65 years with severe or moderately severe haemophilia B (FIX:C ≤ 2, n = 50) and ≥12 bleeding episodes (including ≥6 haemarthroses episodes) within 12 months of study participation were enrolled in this mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 24 publications
(55 reference statements)
11
87
1
5
Order By: Relevance
“…Both prophylaxis regimes had significantly reduced ABR compared to on-demand therapy (p < 0.0001), while no significant differences were observed between prophylaxis regimens (p = 0.22) [5]. In order to better assess the efficacy and safety of once-weekly prophylaxis with BeneFIX ® compared with on-demand, 25 male patients (age 12-65 years) with moderately severe to severe hemophilia B (FIX:C ≤ 2%), ≥ 12 bleeding episodes in the previous 12-months and ≥ 100 exposure days to FIX, were enrolled in a pivotal, multicenter, open-label trial [6].…”
Section: For the Treatment Of Italian Patients With Hemophilia B: A Bmentioning
confidence: 85%
See 2 more Smart Citations
“…Both prophylaxis regimes had significantly reduced ABR compared to on-demand therapy (p < 0.0001), while no significant differences were observed between prophylaxis regimens (p = 0.22) [5]. In order to better assess the efficacy and safety of once-weekly prophylaxis with BeneFIX ® compared with on-demand, 25 male patients (age 12-65 years) with moderately severe to severe hemophilia B (FIX:C ≤ 2%), ≥ 12 bleeding episodes in the previous 12-months and ≥ 100 exposure days to FIX, were enrolled in a pivotal, multicenter, open-label trial [6].…”
Section: For the Treatment Of Italian Patients With Hemophilia B: A Bmentioning
confidence: 85%
“…Currently in Italy, three rFIX are available for treatment of hemophilia B: nonacog alfa (BeneFIX BeneFIX ® (nonacog alfa) was the first rFIX to get marketing authorization in 1997. Efficacy and safety of two prophylaxis regimens (50 IU/kg twice weekly and 100 IU/kg once weekly) vs on-demand therapy were evaluated in a multicenter, randomized, open-label trial conducted on patients with moderately severe to severe hemophilia B (FIX:C ≤ 2%) [5]. Fifteen male subjects (age 6-65 years) with ≥ 12 bleeding episodes within 12 months of study participation were enrolled; the study included four periods: 1) a 16-week on-demand treatment; 2) randomization and 16-week prophylactic treatment with BeneFIX ® 50 IU/kg twice weekly or 100 IU/kg once weekly, 3) a 8-week on-demand treatment, 4) cross-over and 16 weeks receiving the alternate study prophylactic regimen.…”
Section: For the Treatment Of Italian Patients With Hemophilia B: A Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Study 304 (N ¼ 34) compared the bioequivalence of original and reformulated nonacog alfa and evaluated the efficacy and safety of the new formulation during 6-12 months of open-label on-demand treatment or prophylaxis of previously treated patients at least 12 years of age with moderately severe or severe haemophilia B [26]. Study 400 (N ¼ 50) was a phase 4, randomized, open-label, four-period crossover study that compared prophylactic and on-demand treatment with nonacog alfa in previously treated patients aged 6-65 years with moderately severe or severe haemophilia B [32]. The four periods included 16 weeks of on-demand treatment, randomization to a prophylactic regimen (50 IU/kg twice weekly or 100 IU/kg once weekly) for 16 weeks, a subsequent 8-week, on-demand treatment period and a final crossover to the alternative prophylactic regimen for 16 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The design and primary results of this study have been reported previously 11. In brief, patients received on-demand treatment with nonacog alfa for 16 weeks, with dosing adjusted based on the investigator's judgment, according to body weight and bleeding severity (Period 1).…”
Section: Methods and Patientsmentioning
confidence: 99%